Demographic Characteristics of Agricultural Scientists in India: A Study - Singh, K. P. (Journal of Information and Knowledge, 2015)
The paper is an outcome of the research study on demographic characteristics of agricultural scientists working in the ICAR institutions of Delhi and Punjab Agricultural University, Ludhiana’. Data has been collected through a structured questionnaire. The study discusses the various attributes of agricultural scientists such as gender, age, designation, field of specialisation, purpose of research, etc agricultural scientists. The study found that out of 375 respondents more than 89 percent respondents were to male and the while remaining 11 percent were female.